Finančni prihranek in ekološki učinki obdelave posnemkov iz sekundarnega litja v tovarni Impol, d.d. - Kevorkijan, Varužan (Kovine zlitine tehnologije, 1999)
In primary and secondary smelting, in casting-houses and foundries, the generation and treatment of dross entails high costs, both financial and in terms of lost metal. Intelligent melt and dross management can reduce these costs and correspondingly increase profits. This article describes an integral approach to the problem performed in IMPOL d.d., beginning with the suppression of dross formation and considering also its treatment, recovery of metal, and salt cake recycling. The most important constituent of dross is aluminum itself, and it is important to recover as much as possible. In IMPOL d.d. dross is treated immediately after skimming, using an ALTEK press to recover some drain metal in-house. Several important advantages of this pressing treatment are described, and its economic benefits are also demonstrated. Recommendations are also given for further salt cake processing. Secondary dross processing mostly involves two different approaches: hot treatment in the rotary furnace (with or without salt fluxes) or cold mechanical separation into fractions in the tumbler. Both processes are described and compared. The applied technology is economically attractive because of the high value of the metal recovered and the added value of the pressed skulls. It also provides several environmental benefits based on a closed process loop, the relatively low energy requirement of the secondary industry and the possible formation of an environmentally sound non-metallic residue product.
Keywords: pridobivanje aluminija; žlindra; regeneracija